A educação física no processo de inclusão da pessoa com deficiência no contexto escolar - Cardoso Neto, Azor [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The process of inclusion of the PCD student in the school goes through a process of improvement and adaptations every day, when we talk about this process we have to remember how important the participation of all students in this teaching model is. The training of teachers in education is a very comprehensive subject, but when it comes to the training of the same professional to work with children with disabilities, whether physical or intellectual, there are still many studies. Works reviewed in the literature recently on the subject show us a path to the process of inclusion with tutoring in schools. The theme of the study was to bring to light the inclusion process, its difficulties and its solutions to make the school more inclusive every day, so the objective of the present study was to analyze in the literature studies that present us with the history of the inclusive process that has been taking place. in the discipline Physical Education in the school system, aiming to identify how the inclusion of PWD in the dynamics of classes is taking place. It is concluded that it is extremely important to continue to disseminate valid information to promote social awareness and inclusion in schools, whether private or state, and thus ensure that all their rights are actually met.

O processo de inclusão do aluno PCD na escola vem a cada dia passando por um processo de melhoria e adaptações, quando falamos deste processo temos que lembrar do quanto é importante a participação de todos os alunos neste modelo de ensino. A formação de professores em educação é um assunto bastante abrangente, porém quando se fala da formação do mesmo profissional para atuar com crianças com deficiência, seja ela física ou intelectual, cabem ainda muitos estudos. Trabalhos revisados na literatura recentemente, sobre a temática nos indicam um caminho para o processo de inclusão com os trabalhos de tutoria nas escolas. O tema do estudo foi trazer à tona o processo de inclusão, suas dificuldades e suas soluções para tornar a escola cada dia mais inclusiva, sendo assim o objetivo do presente estudo foi analisar na literatura estudos que nos apresenta o histórico do processo inclusivo que vem ocorrendo na disciplina Educação Física no sistema escolar, visando identificar como está ocorrendo a inclusão da PCD na dinâmica das aulas. Conclui-se que é de extrema importância continuar a disseminar informação válida para promover a consciência social e a inclusão nas escolas seja ela particular, ou estadual, e assim garantir que todos os seus direitos sejam de fato atendidos.
Physical education in the process of inclusion of people with disabilities in the school context
Keywords: Physical education; People with disabilities; Education; Inclusão; Educação física; Deficientes; Educação